Musyrifah Strategy in the Management of Mutawassith Class on Mufrodat Material at Shabah Al-Lughah - Maziyah, Ri'ayatul; Jannah, Arina Nur; Mufidah, Isti; Arifa, Zakiyah (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2019)
Classroom management in the Shabah al-Lughah program has many variations on each subject and meeting. But there are also problem mufrodat learning in the classroom that are overcome by the teacher variation of strategies.  his study aims to determine the strategy and role of supervisor (musyrifah) in the process of mufrodat learning on the mutawassith class so that it was categorized as a good classroom management. The type of this research is qualitative descriptive researchobtained from interviews, observation, and documentation relating to the strategy and role of musyrifah in measuring mutawassith class on the mufrodatmaterial; thenit analyzed. The data sources in this study are the musyrifah who teach in the mutawassith class. The results of this study are; first, variations strategy of musyrifah on the management of the mutawassith class when the mufrodat learning isusingthe audiolingual, the grammatical, the direct, the question, and answer method and the discussion. Second, the role of musyrifah in the classroom is more often teacher-centered, that ismusyrifah acts as an instructor, musyrifah arranges to seat, delivers material, minimizes the transition time, gives a clue when mahasantrimention mufrodat meaning.Musyrifah dominates speech while Learner-centered roles are rarely used. So the existence of this research can provide a solution for instructors of Arabic language to develop their strategies, so that the desired goals of mufrodat material can be achieved.